St. Louis Paper - Ore-dressing Practice in the Joplin District (with Discussion) - C. A. Wright (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
The average lead and zinc content of the ores mined and milled in the Joplin district is low as compared with that of other lead and zinc deposits throughout the United States. Because of this fact and of the high grade of the concentrates, the ratio of concentration is unusually high. Most of the operating companies have aimed to produce as high a grade of concentrate as possible in order to obtain the highest price for their product. They have done this at the sacrifice of the percentage of zinc recovered. The average percentage of zinc recovery is from 60 to 70 per cent. For percentage of recoveries from actual mill tests, see tables. The concentration is commonly effected by crushing the ore to ½-in. (12.7 mm.) size and subjecting it to a roughing and cleaning over two or more large Cooley jigs, of the Harz type, the finer sands being treated on the usual types of sand and slime tables. The treatment of slimes by flotation is being tested at several of the larger mills. Coarse Concentration When the ore has been hoisted from the mine it is dumped onto a chute leading to a grizzly made of iron bars, usually heavy rails, spaced 4 to 5 in. (101 to 127 mm.) apart. The oversize is caught on the grizzly, the mineralized pieces are broken with sledge hammers so as to pass through, and the boulders that are practically barren are sorted out by hand and trammed to the waste-rock pile. The proportion of waste rock thus sorted out varies from a fraction of 1 per cent. to 15 per cent., depending on the nature of the rock. Crushing The undersize material, 5 in. (127 mm.) or less in diameter, passes through the openings of the grizzly into the mill hopper below. From